Digitalisierung und Weiterbildung Beiträge zu erwachsenenpädagogischen Forschungs- und Entwicklungsfeldern - Robak, Steffi Prof. Dr; Asche, Eike Dr; Kühn, Christian; Heidemann, Lena Dr; Rommel, Irina Dr; Sander-Böving, Hanna; Held, Johanna; Grönemeyer, Kerstin; Bunk, Marie; Preuß, Jessica; Rieckhoff, Marina; Ludwig, Sophia; et al. (Verlag Barbara Budrich, 2022)
How does digitization affect adult and further education? The book shows the range of research perspectives and fields of application. Based on basic theoretical research approaches, specific subject areas and application-related projects for the design of media-supported teaching-learning concepts are taken up. The contributions show the relevance of educational research for the design of the digital transformation. Interdisciplinary fields of research and application are designed that cannot do without well-founded adult education perspectives.